Assessing English Learning Motivation among Thai University Students: A Cross-Faculty Perspective - Hendrajaya, Muhammad Reza (English Education Department, Universitas Islam Indonesia, 2023)
This study delves into Thai university students' motivation to learn English as a Foreign Language (EFL). The research involved 33 participants from a Thai research university, with 15 students from the Faculty of Engineering (EG) and 18 from the Faculty of Liberal Arts (LA). The main objectives were to (1) identify the primary motivation underlying students' willingness to learn English, (2) identify the differences in motivation between EG and LA students, and (3) verify that students' milieu has a role in their motivation. The study employed a questionnaire on attitudinal constructs—integrative and instrumental motivation. Additionally, three open-ended questions were used. Results revealed that (1) both student groups displayed higher scores in integrative motivation, (2) while no significant differences were observed in motivation underlying students' willingness to learn English, LA students exhibited higher scores in both motivations compared to EG students, and (3) milieu played a pivotal role in shaping students' motivation to learn English. Furthermore, this study has significant implications for educators, emphasizing the necessity of acknowledging and addressing students' unique motivations and goals across various majors. While both groups exhibit integrative motivation, instrumental motivation provides additional support.